Polyploid induction in selected Mung Bean (Vigna radiata L. Wilczek) genotypes (Agriculture, Food, and Natural Resources Journal, 2024)
This experiment was conducted to evaluate the effects of different immersion periods of colchicine 0.2% solution on the seeds of three mung bean accessions. The experiment was a 3×3 factorial experiment in  complete randomized design and the significant means were separated using least significant difference (LSD) at 5% probability level. The experiment was replicated three times. The immersion periods were: 2 and 4 hours while ordinary water was used as control and the accessions of mung bean were Tvr 72, Tvr 77 and Tvr 98. The different mung bean accessions and their seeds immersion periods in colchicine 0.2% solution showed no significance difference (p≤0.05) on days to germination, emergence and 50 % flowering respectively. The three mung bean accessions in two hours immersion relatively produced higher values of all the measured parameters than 4 hours immersion. The number of leaves, plant heights, stem girth and number of pods did not significantly vary in  Tvr 77 and Tvr 98 cochiploids of two hours immersion. The Tvr 77 although closely followed by Tvr 98 produced the largest measured leaf area (192cm2) and longest pods (11cm) and largest number of seeds (15). We therefore recommend the multiplication and use of Tvr 77 and Tvr 98 cochiploids for mung bean seed production and further breeding.
Keywords: Accessions; Breeding; Cochiploids; Colchicine; Mung bean; Seeds